IncN plasmids carrying bla CTX-M-1 in Escherichia coli isolates on a dairy farm - Dolejská, Monika; Jurčíčková, Zuzana; Literák, Ivan; Pokludová, Lucie; Bureš, Jiří; Hera, Alfred; Kohoutová, Ludmila; Smola, Jiří; Čížek, Alois (Veterinary microbiology, 2011)
The aim of the study was to compare the prevalence of extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli bovine isolates on a conventional dairy cattle farm with high consumption of parenteral and intramammary cephalosporins (farm A) and on an organic dairy farm with no cephalosporin use (farm B). ESBL-producing E. coli were isolated from rectal swabs and milk filters by selective cultivation on MacConkey agar with cefotaxime (2mg/l). ESBL genes were identified by polymerase chain reaction (PCR) and sequencing, and the genetic diversity of the isolates was determined by XbaI pulsed field gel electrophoresis (PFGE). Conjugative transfer, incompatibility group, and restriction fragment length polymorphism (RFLP) profiles of the ESBL-carrying plasmids were studied. Higher prevalence (39%, n(rectal samples in cows)=309) of CTX-M-1-producing E. coli isolates was found on farm A compared to farm B (<1%, n(rectal samples in cows)=154; 0%, n(rectal samples in calves)=46). Using PFGE, the isolates from farm A were divided into nine pulsotypes. In all ESBL-positive isolates, the bla(CTX-M-1) gene was carried on 40 kb IncN conjugative plasmids of three related HincII restriction profiles. Horizontal gene transfer through transmission of IncN plasmids harboring bla(CTX-M-1) as well as clonal dissemination of a particular clone seems to be involved in dissemination of CTX-M-1-producing E. coli isolates in cows on the farm using cephalosporins in treating bacterial infections. The study demonstrates a possible role of cephalosporin use in the widespread occurrence of CTX-M-1-producing E. coli on the conventional dairy cattle farm compared to the organic farm.
Keywords: Electrophoresis, Gel, Pulsed-Field; přenos genů horizontální; Gene Transfer, Horizontal; Escherichia coli Proteins; Czech Republic; infekce vyvolané Escherichia coli; zvířata; Animals; Escherichia coli Infections; Plasmids; Polymerase Chain Reaction; Female; polymorfismus délky restrikčních fragmentů; DNA bakterií; beta-Lactamases; rezistence k cefalosporinům; nemoci skotu; plazmidy; beta-laktamasy; Escherichia coli; DNA, Bacterial; ženské pohlaví; pulzní gelová elektroforéza; Cattle Diseases; Cephalosporins; Polymorphism, Restriction Fragment Length; skot; polymerázová řetězová reakce; Cattle; Česká republika; proteiny z Escherichia coli; cefalosporiny; Cephalosporin Resistance